Tecnologia social na escola : alimentação saudável e uso do fogão solar - Alves, Erica Costa (2019)
The school environment can contribute to the dissemination of health promoting attitudes, leading the student to understand the importance of good food choices and the danger of lack of food and nutritional security. The influence of the media and the ease of obtaining fast-foods, thus leading to an increase in the index of people with hypertension and diabetes (Santos, 2012), is the Brazilian food standard. ), this conclusion motivated the interest to carry out this work. We outline as a general objective to analyze the promotion of "Social Technology" in the school through the construction and use of a solar cooker, favoring the awareness of sustainable practices and promoting the reuse of food. The use of the solar cooker, as an alternative to cooking food, contemplates solar energy that is renewable and presents no ecological damages, avoiding environmental aggressions (Filho, 2011), but also empowers the student of activities / actions that generate appreciation for the environment school. In addition, it allows methodologies to develop content that teachers can use in the classroom and reveals a way that "Social Technology" can be contemplated. The work wanted to collaborate for the insertion of "Social Technologies" in school. In order to meet the objectives, the research consisted of "participant observation" (Minayo, 2004) for the production of data and questionnaires were applied to the investigated public, as a support tool, to diagnose the researched environment. The aim of this study was to investigate the food situation of students and the characteristics of school meals, and later three workshops were developed: the first with a nutritional professional on food and food safety, the second with lecture and the construction of a solar cooker, to be used in the next workshop and the third was to present recipes with food utilization and production of eggshell meal and banana peel that were introduced as ingredients in school meals. Flours were produced by drying the shells with the use of the solar cooker, produced in the second workshop. The results indicate that students have deficient food choices, so the implementation of actions involving Food Education is relevant to the nutritional needs of the school population. The activity of flour production and stove monitoring contributed to the student's belonging and empowerment. Actions such as these are important to publicize the work with "Social Technologies" in schools. The idea of building the solar cooker in school presents possibilities not only for the biology teacher, but also for physics, chemistry, mathematics, etc. Teachers can also use this material to explore their optics, refraction, organic chemistry classes in food processing classes, etc. In addition, the solar cooker enables the realization of sustainable practices and its use can be considered as a product that reflects the work with "Social Technology", besides promoting, in the school, an approximation of theory with practice, expanding scientific knowledge of the student. Raising awareness about the use of solar cookers gives rise to new reflections, allowing a rethink about how "Social Technology" can contribute to the school curriculum, the community and, consequently, the role of the student involved in this process.